An unconventionally secreted effector from the root knot nematode Meloidogyne incognita, Mi‐ISC‐1, promotes parasitism by disrupting salicylic acid biosynthesis in host plants. (19th December 2021) - Qin, Xin; Xue, Bowen; Tian, Haiyang; Fang, Chenjie; Yu, Jiarong; Chen, Cong; Xue, Qing; Jones, John; Wang, Xuan
Abstract: Plant‐parasitic nematodes need to deliver effectors that suppress host immunity for successful parasitism. We have characterized a novel isochorismatase effector from the root‐knot nematode Meloidogyne incognita, named Mi‐ISC‐1. The Mi‐isc‐1 gene is expressed in the subventral oesophageal glands and is up‐regulated in parasitic‐stage juveniles. Tobacco rattle virus‐induced gene silencing targeting Mi‐isc‐1 attenuated M. incognita parasitism. Enzyme activity assays confirmed that Mi‐ISC‐1 can catalyse hydrolysis of isochorismate into 2, 3‐dihydro‐2, 3‐dihydroxybenzoate in vitro. Although Mi‐ISC‐1 lacks a classical signal peptide for secretion at its N‐terminus, a yeast invertase secretion assay showed that this protein can be secreted from eukaryotic cells. However, the subcellular localization and plasmolysis assay revealed that the unconventional secretory signal present on the Mi‐ISC‐1 is not recognized by the plant secretory pathway and that the effector was localized within the cytoplasm of plant cells, but not apoplast, when transiently expressed in Nicotiana benthamiana leaves by agroinfiltration. Ectopic expression of Mi‐ISC‐1 in N . benthamiana reduced expression of the PR1 gene and levels of salicylic acid (SA), and promoted infection by Phytophthora capsici . The cytoplasmic localization of Mi‐ISC‐1 is required for its function. Moreover, Mi‐ISC‐1 suppresses the production of SA following the reconstitution of the de novo SA biosynthesis via the isochorismate pathway in the cytoplasm of N. benthamiana leaves. These results demonstrate that M. incognita deploys a functional isochorismatase that suppresses SA‐mediated plant defences by disrupting the isochorismate synthase pathway for SA biosynthesis to promote parasitism. Abstract : The nematode effector from the root‐knot nematode Meloidogyne incognita, Mi‐ISC‐1, diverts the cytoplasmic isochorismate away from conjugation to l ‐glutamate, thus interrupting salicylic acid biosynthesis in the cytosol.